A convenient 3D reconstruction model based on parallel-axis structured light system. (March 2021) - Zhang, Jing; Luo, Bin; Su, Xin; Li, Lu; Li, Beiwen; Zhang, Song; Wang, Yajun
Highlights: A convenient coaxial structure-light 3D reconstruction model is proposed. The proposed coaxial system can be easily calibrated with the aid of a productive matrix. This method is easy-to-implement and efficient compared with conventional methods High-accuracy 3D shape measurement is achieved with the aid of a sideway. Abstract: Conventional high-accuracy three-dimensional (3D) reconstruction methods usually involve complicated and time-consuming system calibration. This paper presents a novel and simple 3D reconstruction model based on a parallel-axis structured light system. Compared to the traditional structured light system, the proposed system contains a perspective projection unit and a telecentric imaging unit. Instead of obtaining the complicated structured light system parameters, the proposed model only requires the retrieval of a product matrix which could be easily calibrated by using an ordinary white plane. For an arbitrary point A on the object surface, it is mathematically proved that the product matrix of its phase map and height distribution is proportional to the distance between A and projector optical center in XY plane, and independent of the depth in Z direction. Experiments were carried out to measure a step-height object and a cylindrical surface, and the results verify that the proposed method can achieve high-accuracy 3D shape measurement.